STRATEGI PENYELESAIAN TINDAK PIDANA PENCURIAN MELALUI RESTORATIVE JUSTICE - Ica Karina (Fiat Iustitia : Jurnal Hukum, 2025)
Theft is one of the most common crimes and causes both material and immaterial losses for victims and the community. Theft cases have generally been resolved through criminal justice mechanisms focused on punishing the perpetrator. However, this model often fails to provide a comprehensive sense of justice and fails to address the root causes of the problem. Restorative justice offers an alternative approach that emphasizes restoration by directly involving the perpetrator, victim, and community. Applying restorative justice to theft cases can restore social relationships, provide satisfaction to victims, and encourage perpetrator accountability without compromising legal certainty. Therefore, restorative justice can be a more humane and solution-oriented option in handling theft cases.